Developing an index of EX-POST parliamentary oversight of public finance. Issue 1 (2nd January 2019) - Stapenhurst, Rick; Jacobs, Kerry; Cedric Eboutou, Thomas
ABSTRACT: For the past decade, scholars and practitioners have developed indexes to measure both legislative powers in general, and of the legislative power of the purse, in particular. Initial focus was on the development of a comprehensive index of legislative powers, and on assessing the ex-ante role of the legislature in the budget process. This article substantially deepens extends previous research on ex-post oversight, by developing a more comprehensive index to measure ex-post oversight, by using more up-to-date data bases and by including more countries. We can partially confirm the emerging consensus that ex-post budget oversight is stronger in parliamentary – and especially Westminster – systems than in countries with other forms of government, thereby somewhat offsetting the previously identified weaknesses of Westminster parliaments in budget formulation. When used in combination Wehner's [2006. Assessing the power of the purse: An index of legislative budget institutions. Political Studies, 54, 767–785] index of ex-ante legislative oversight, this index provides a comprehensive picture of legislative power of the purse regarding the budget process.